2012
DOI: 10.1051/0004-6361/201118496
|View full text |Cite
|
Sign up to set email alerts
|

Oscillation mode linewidths of main-sequence and subgiant stars observed byKepler

Abstract: Context. Solar-like oscillations have been observed by Kepler and CoRoT in several solar-type stars. Aims. We study the variations in the stellar p-mode linewidth as a function of effective temperature. Methods. We study a time series of nine months of Kepler data. We analyse the power spectra of 42 cool main-sequence stars and subgiants using both maximum likelihood estimators and Bayesian estimators to recover individual mode characteristics such as frequencies, linewidths, and mode heights. Results. We repo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
117
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(141 citation statements)
references
References 32 publications
23
117
1
Order By: Relevance
“…Using CoRoT data, Baudin et al (2011) have found that τ max scales approximately as T −m eff where m = 16.2 ± 2 for the main-sequence and sub-giant stars. Recently, Appourchaux et al (2012) have found a slope m = 15.5 ± 1.6 with Kepler data, which is hence compatible with that of Baudin et al (2011). Such a power law is also supported by the theoretical calculations of Belkacem et al (2012) performed for main-sequence, sub-and red giant stars.…”
Section: Theoretical Scaling Relation For the Velocity Mode Amplitudesupporting
confidence: 74%
“…Using CoRoT data, Baudin et al (2011) have found that τ max scales approximately as T −m eff where m = 16.2 ± 2 for the main-sequence and sub-giant stars. Recently, Appourchaux et al (2012) have found a slope m = 15.5 ± 1.6 with Kepler data, which is hence compatible with that of Baudin et al (2011). Such a power law is also supported by the theoretical calculations of Belkacem et al (2012) performed for main-sequence, sub-and red giant stars.…”
Section: Theoretical Scaling Relation For the Velocity Mode Amplitudesupporting
confidence: 74%
“…Previous observations did not report a similar T eff dependence [4]. On the contrary, this kind of T eff dependence was firmly established for main-sequence and subgiant stars [1,4]. However, we find a power law with a small exponent, whereas a high value is observed for the other solar-like pulsators, so that our results are far from the ones observed for main-sequence stars.…”
Section: The γ 0 -T Eff Relationcontrasting
confidence: 99%
“…Individual mode widths (Γ 0 ) were computed following [1] for each of the stars. A mean value of Γ 0 is derived from the weighted average of the width of the three radial modes closest to ν max .…”
Section: Measurement Of the Star Radial Mode Linewidthsmentioning
confidence: 99%
“…(1) in Appourchaux et al (2014) and Eq. (2) in Appourchaux et al (2012). Next, the background power spectral density, B(ν), across the frequency range occupied by the modes is dominated by contributions from granulation and shot noise.…”
Section: Pulsation Frequenciesmentioning
confidence: 99%